Interannual and Seasonal Variations in Estuarine Water Quality - Costa, Cibele R.; Costa, Monica F.; Dantas, David V.; Barletta, Mario (Frontiers in Marine Science, 2018)
Anthropic processes degrade quality of estuarine environments, resulting in a worrying form of water pollution. The objective of the study was to describe and discuss interannual and seasonal changes of water quality based on indicators monitored in Goiana River estuary, as well as identifying the main drivers of such changes. We considered three estuarine areas or habitats (upper estuary, middle estuary and lower estuary), and two seasons (dry and rainy) for anchoring sample design. The information collected for surface and bottom water include water temperature (°C), salinity, dissolved oxygen (mg L−1), saturation (%) and Secchi depth (cm) (n = 864). The monthly total rainfall (mm) was compiled from public database. Multivariate analyses highlight inter dependency among these parameters. Water quality was reduced in dry periods (including episodes of hypoxia), but generally increased toward the mouth of estuary. Rainfall is the most important factor in the renewal and maintenance waters of small tropical estuaries. Regions most sensitive to climate change where water resources are depleted and/or compromised should pay even more attention to upcoming changes in rainfall (seasonal) and climatic patterns in addition to better water management practices.